TRADITION AND COGNITIVE APPROACHES IN SYNTAX ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This scientific article aims to provide a comprehensive overview of syntax, a fundamental component of linguistics concerned with the structure, organization, and arrangement of words and phrases in a language. The article explores both traditional and cognitive approaches to syntax, examining their underlying principles and methodologies. By highlighting the main units of syntax, including phrases, sentences, and constituents, this paper seeks to contribute to a deeper understanding of the complexities and intricacies of language structure.